A globalização e seus críticos - Luís Antonio Groppo (Ciências Sociais Unisinos)
The article intends to demonstrate the importance of the social, economical, political and cultural processes that the word globalization seems to designate, but first it sketches a critique of the ideological use of that word. It discusses some movements that are critical of the hegemonic globalization. Although they are still not able to implement "another globalization", they certainly can indicate many causes of the suffering of humankind and the planet.